Image Compression Using Hybrid Technique - Singh, Paramjeet; Garg, Binni; Rani, Shaveta (International Journal of Computer Sciences and Engineering, 2025)
Image compression is a technique to reduce the file size of an image. The main objective of a compression algorithm is to remove redundancy in an image. Compression ratio and Peak signal to noise ratio (PSNR) are the two parameters used to evaluate the efficiency of a particular algorithm. In this paper, we introduce some popular and a new compression algorithm. Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are the existing algorithms used for image compression. Hybrid compression is a new algorithm which is a combination of DWT and DCT. It takes advantages of both DWT and DCT by discarding their limitations. The purpose of the hybrid algorithm is to keep the balance between compression ratio and quality of the reconstructed image. On comparison of results of the Hybrid compression algorithm with DWT-based compression algorithm, it shows that there are high compression ratio and high quality of reconstructed image using Hybrid compression.